Concanavalin A staining: a potential biomarker to predict cytarabine sensitivity in acute myeloid leukemia - Zhang, Tao; Marsman, Glenn; Pereira-Martins, Diego A.; Wuhrer, Manfred; Huls, Gerwin A.; Wiersma, Valerie R. (Frontiers in Hematology, 2024)
Acute myeloid leukemia (AML) is a cancer of the myeloid lineage of blood cells, with an overall 5-year survival rate of 25%, mainly due to therapy-resistant relapses in >50% of patients. Standard treatment of AML comprises cytarabine (AraC) with anthracyclines. Biomarkers to determine AraC sensitivity are currently lacking, hampering the rational choice of optimal treatment protocols, which would be especially warranted in case of primary refractory disease. In the current study we hypothesized that AraC-resistant AML cells harbor a different 'sugar decoration', i.e. glycosylation profile, compared to sensitive cells, that can be used as biomarker for AraC sensitivity. Therefore, we analyzed the expression of glycosylation-related genes in publicly available AML datasets, whereby mannosylationrelated genes (6 out of 13) significantly associated with worse survival in patients treated with AraCbased intensive chemotherapy protocols. In line with this data, AraC-resistant AML cells expressed higher levels of high mannose N-glycans as detected by mass spectrometry-based glycomics.Conconavalin A (ConA), a lectin that specifically recognizes α-mannosed in N-glycans, bound stronger to AraC-resistant cells, and the extent of ConA-binding correlated with AraC sensitivity in a panel of AML cell lines. Furthermore, the ConA-staining could discriminate AraC sensitivity in vitro between two patient-derived AML samples taken at diagnosis. Therefore, the ConA-staining may be a potential novel biomarker to predict AraC sensitivity in AML.